Cardiorespiratory fitness is associated with white matter integrity in aging. Issue 6 (24th April 2015) - Hayes, Scott M.; Salat, David H.; Forman, Daniel E.; Sperling, Reisa A.; Verfaellie, Mieke
Abstract Objective Aging is associated with reduced neural integrity, yet there are remarkable individual differences in brain health among older adults (OA). One factor that may attenuate age‐related neural decline is cardiorespiratory fitness (CRF). The primary aim of this study was to link CRF to neural white matter microstructure using diffusion tensor imaging in OA. Methods Young adults (YA; n = 32) and OA (n = 27) completed a graded maximal exercise test to evaluate CRF and diffusion tensor magnetic resonance imaging to examine neural white matter integrity. Results As expected, pervasive age‐related declines in white matter integrity were observed when OA were compared to YA. Further, peak VO2 was positively associated with fractional anisotropy (FA), an indicator of white matter integrity, in multiple brain regions in OA, but not YA. In multiple posterior regions such as the splenium, sagittal stratum, posterior corona radiata, and superior parietal white matter, FA values were similar in YA and OA classified as higher fit, with both groups having greater FA than lower fit OA. However, age‐related differences in FA values remained in other regions, including the body and genu of the corpus callosum, precuneus, and superior frontal gyrus. Interpretation CRF is positively associated with neural white matter microstructure in aging. The relationship between peak VO2 and FA appears to be tract‐specific, as equivalent FA values were observed in higher fit OA and YA in some white matter tracts, but not others. Further, the association between peak VO2 and FA appears to be age‐dependent.